Design of triple cogeneration system for hydrogen fuel cell in greenhouse based on resource analysis - Yang, Jinlong; Li, Rui; Lee, Chul-Hee (Frontiers in Energy Research, 2023)
Introduction: Hydrogen energy has a massive advantage in the energy supply mode regarding greenhouse gas emissions. Nevertheless, the energy supply system needs to be redesigned to meet the heating/cooling needs and the goals of using hydrogen energy. Methods: The comprehensive utilization efficiency of system energy can be improved using resource analysis to solve the problem of waste heat and formulate a technical plan for triple cogeneration of hydrogen greenhouse. Results: By calculation, the energy efficiency of the coal boiler heating system, the hydrogen energy heating system and the hydrogen greenhouse triple heating system are 65%, 52.93%, and 73.36%, respectively. Compared to the coal boiler heating system and the hydrogen energy heating system, the advantages of the hydrogen greenhouse triple cogeneration system are that the comprehensive utilization efficiency of the system energy has been improved, and no CO2 is generated when it works, which does not cause pressure on environmental protection. At the same time, the exergy efficiency of the hydrogen greenhouse triple cogeneration system is higher. Currently, due to the high price of hydrogen and fuel cells, the economic advantages are not outstanding. Still, coal energy is expected to be replaced in the future with the continuous decline in the cost of hydrogen and fuel cells. According to the current coal price, when the hydrogen price decreases to below 1.3/kg, coal will lose its price advantage in terms of fuel. At the same time, hydrogen has a high energy density, small volume, and low transportation cost. According to IRENA and Hydrogen Council, the cost of producing hydrogen from renewable energy will drop to 1/kg by 2050. The system will significantly reduce the operating costs of greenhouses in the future. Discussion: As a result, the hydrogen greenhouse triple cogeneration system is suitable for producing greenhouse agriculture and the heating method of fossil fuel combustion that will replace coal in the future.